Carl Maria von Weber and the search for a German opera - Meyer, Stephen C., 1963- (Indiana University Press, 2003)
Stephen C. Meyer details the intricate relationship between the operas Der Freischütz and Euryanthe, and the contemporary discourse about the 'Germany of the imagination' and the new nation itself. In doing so, he presents excerpts from a wide range of philosophical, political, and musical writings, many of which are little known and otherwise unavailable in English. Individual chapters trace the multidimensional concept of German and 'foreign' opera through the 19th century.